Copper-Catalyzed Intramolecular Desymmetric Aryl CO Coupling for the Enantioselective Construction of Chiral Dihydrobenzofurans and Dihydrobenzopyrans - Yang, Wenqiang; Liu, Yangyuan; Zhang, Shasha; Cai, Qian (Angewandte Chemie International Edition, 2015)
O‐Heterocyclic structures such as 2,3‐dihydrobenzofurans are key motifs in many natural compounds and pharmaceuticals. Enantioselective formation of chiral dihydrobenzofurans and analogues was achieved through a copper‐catalyzed desymmetrization strategy with a chiral cyclic 1,2‐diamine. A broad range of substrates are compatible with this CuI‐diamine catalytic system and afford the desired coupling products with chiral tertiary or quaternary carbon centers in high yields and good to excellent enantioselectivities under mild conditions. O‐Heterocyclic structures such as chiral dihydrobenzofurans can be formed enantioselectively through a copper‐catalyzed desymmetrization strategy with a chiral cyclic 1,2‐diamine ligand. A broad range of substrates is compatible with this CuI‐diamine catalytic system and afford the desired coupling products with chiral tertiary or quaternary carbon centers in high yields and good to excellent enantioselectivities under mild conditions.